2010
DOI: 10.2522/ptj.20090092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work-Related Pain on Physical Therapists and Occupational Therapists

Abstract: Work-related pain affects therapists in several personal and professional domains. It also may affect career plans. Strategies to reduce the risk of injury and physical loading of jobs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 21 publications
4
32
0
6
Order By: Relevance
“…However, fitness levels of physiotherapists have not been well explored in many developing countries like Ghana, warranting the need to investigate the fitness levels of physiotherapists working in urban areas of Ghana. Previous studies have suggested that physiotherapists are usually susceptible to work-related musculoskeletal disorders [7, 8]. Similarly, an assessment of the components of PF by Gorner et al [9] reported that low levels of physical activity among physiotherapy undergraduate students was accompanied by lower level of aerobic capacity than that obtained in their physical education counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…However, fitness levels of physiotherapists have not been well explored in many developing countries like Ghana, warranting the need to investigate the fitness levels of physiotherapists working in urban areas of Ghana. Previous studies have suggested that physiotherapists are usually susceptible to work-related musculoskeletal disorders [7, 8]. Similarly, an assessment of the components of PF by Gorner et al [9] reported that low levels of physical activity among physiotherapy undergraduate students was accompanied by lower level of aerobic capacity than that obtained in their physical education counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…There are hundreds of studies on WMSDs among nurses and other health care workers, but we only identified nine studies investigating WMSDs among American Physical Therapists (PTs) and none of them were conducted in Florida [3][4][5][6][7][8][9][10]. Even though PTs may have more indepth knowledge and receive more training on proper body mechanics, they perform many of the same physically demanding and repetitive tasks completed by nurses, being exposed to some of the same occupational risks.…”
Section: Introductionmentioning
confidence: 98%
“…Physiotherapists have traditionally been viewed by themselves and others, as immune from MSI owing to a perception that expertise, knowledge and skill in patient handling would offer protection from injury (Campo & Darragh 2010). In addition, research (Tyson et al.…”
Section: Discussionmentioning
confidence: 99%